Temperature Dependence of Clumped Isotopes (∆47) in Aragonite. Issue 20 (19th October 2022) - de Winter, Niels J.; Witbaard, Rob; Kocken, Ilja J.; Müller, Inigo A.; Guo, Jingjing; Goudsmit, Barbara; Ziegler, Martin
Abstract: Clumped isotope thermometry can independently constrain the formation temperatures of carbonates, but a lack of precisely temperature‐controlled calibration samples limits its application on aragonites. To address this issue, we present clumped isotope compositions of aragonitic bivalve shells grown under highly controlled temperatures (1–18°C), which we combine with clumped isotope data from natural and synthetic aragonites from a wide range of temperatures (1–850°C). We observe no discernible offset in clumped isotope values between aragonitic foraminifera, mollusks, and abiogenic aragonites or between aragonites and calcites, eliminating the need for a mineral‐specific calibration or acid fractionation factor. However, due to non‐linear behavior of the clumped isotope thermometer, including high‐temperature (>100°C) datapoints in linear clumped isotope calibrations causes them to underestimate temperatures of cold (1–18°C) carbonates by 2.7 ± 2.0°C (95% confidence level). Therefore, clumped isotope‐based paleoclimate reconstructions should be calibrated using samples with well constrained formation temperatures close to those of the samples. Plain Language Summary: Clumped isotope analysis is a highly accurate method for reconstructing temperatures in Earth's past climate from calcium carbonate fossils of calcifying organisms. Unfortunately, calibration studies so far were predominantly based on samples of calcite, a common calcium carbonate mineral. It is therefore unknown whether these clumped isotope calibrations yield accurate temperature reconstructions when applied to aragonite, another carbonate mineral which corals and many shells consist of. Therefore, we grew mollusks that build their shell out of aragonite in a lab at constant water temperatures to test the clumped isotope method on aragonitic shells. We find no significant difference in the temperature sensitivity of the method between our aragonites and the previous calibrations and show that the temperature calibration can be improved by combining data from different minerals. However, we find subtle differences in the temperature dependence of clumped isotopes between hot (>100°C) carbonates and cold (<30°C) carbonates, which cause previous calibrations to underestimate temperatures of colder carbonates. We conclude that using carbonate samples grown at temperatures close to the temperatures of the samples used in climate reconstructions can eliminate a bias of 2.7°C, resulting in more accurate reconstructions of past temperatures. Key Points: Precise control on carbonate formation temperatures enables more accurate clumped isotope‐temperature calibrations Isotopic ordering and acid fractionation in aragonite have a similar temperature dependence as in calcite, enabling combined calibrations The Δ47 − 1 T 2 $-\frac{1}{T^{2}}$ relation in carbonate is non‐linear, therefore adding hot calibration data offsets calibrations in the cold temperature range